COGNITIVE ASPECTS OF MODERN PHILOSOPHY OF HISTORICAL KNOWLEDGE - Spartak Sh. Aytov (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The aim of this work is the intelligent reconstruction and the analysis of the various methodological approaches to cognitive areas of modern philosophy of history and determines their cognitive and academic relationships with conceptual terms of such branches of historical knowledge as historical anthropology. Methodology. Methodological tools of this work are such scientific approaches as methods of philosophy of science, interdisciplinary approach, methods of source and system analysis. Scientific novelty. Reproduced and analyzed was a number of methodological approaches inherent in the natural sciences and the social - the humanities. The latter, in accordance with the principles of interdisciplinary paradigm, is very widely applied by the modern philosophy of historical knowledge, in particular in the analysis of the historical process and its main elements: the mentality, attitudes and norms of socially significant and personal behavior of individuals and societies of the past. The influence of research on various historical and historical anthropological problems such concepts implanted in the methodology of modern philosophy of history scientific disciplines as chaos theory, synergetics, mathematical biology, ethnology, social psychology, etc. Focuses on intellectual connections are used in the philosophy of history, historical knowledge interdisciplinary methodology, theory and concepts of natural science and social - humanities. They are used to analyze and understand the complex and multifaceted historical events and processes. Conclusions. The result of the analysis of the cognitive dynamics applications in the philosophy of history of conceptual approaches of a very wide range of scientific disciplines has been the allocation of a number of phases of the mining process. Each of them has special logic - methodological and socio cultural characteristics ("Data"). Internal, cognitive science dynamics of this unity was not the aiming at the destruction of the previous intellectual tradition, but its deepening and updating on the basis of the implementation of more effective and diverse methodological approaches.